Comparative field experimental investigations of different flat plate solar collectors. (May 2015) - Chen, Guangming; Doroshenko, Alexander; Koltun, Paul; Shestopalov, Kostyantyn
Highlights: Polymeric materials are employed for solar collector construction. Polycarbonate is the prospective material for the solar application. The efficiency of the SC-P is lower compared to the efficiency of traditional one. Environmental impact of SC-P is lower than that of metal SC. Abstract: Full-scale traditional metal solar collectors and solar collector specimens fabricated from polymeric materials were investigated in the present study. A polymeric collector is 67.8% lighter than a traditional metal solar collector, and a metal solar collector with transparent plastic covering is 40.3% lighter than a traditional metal solar collector. Honeycomb multichannel plates made from polycarbonate were chosen to create a polymeric solar collector. A test rig for the natural circulation of the working fluid in a solar collector was built for a comparative experimental investigation of various solar collectors operating at ambient conditions. It was shown experimentally that the efficiency of a polymeric collector is 8–15% lower than the efficiency of a traditional collector. The results of a Life Cycle Assessment study showed the advantages of the application of polymeric materials in the construction of solar collectors.